Effects of family socioeconomic status on home math activities in urban China: The role of parental beliefs. (October 2018) - Pan, Yuejuan; Yang, Qingqing; Li, Yanfang; Liu, Lisha; Liu, Shanshan
Abstract: The present study examined the effects of family socioeconomic status (SES) on home math activities and the role of parental beliefs in the link between family SES and home math activities in urban China by using questionnaires of 885 young children's parents randomly sampled in Beijing. The results showed that family SES has a significantly positive association with the frequency of home math activities, a significantly negative association with parental beliefs on the importance of early math learning in both 'numeracy and quantity' and 'geometry and space', and a significantly negative association with parental beliefs on mastery age in the domain of 'geometry and space' only. The path analysis revealed that family SES has significant direct effects on the frequency of home math activities. Parental beliefs on the importance of early math learning had suppressing effects on the relationship between family SES and home math activities. In addition, parental beliefs on mastery age only partially mediated the relationship between family SES and home math activities in the domain of 'geometry and space'. The results implied that there are significant SES-related differences in home math activities, and different aspects of parental beliefs might play different roles in the association between family SES and home math activities currently in urban China. Highlights: Whether parental beliefs play mediation role in the link between family SES and home math activities may depend on the content and nature of beliefs. Family SES has significantly direct positive effects on Chinese parents' provision of home math activities. Chinese parents' beliefs on the importance of mastering math skills have suppressing effects in the links between family SES and home math activities. Higher SES parents attach less importance to math learning, which will decrease the positive effect of family SES on home math activities. Chinese parents' beliefs on the age to master math skills partially mediated the association between family SES and home math activities in the domain of 'geometry and space', as these are not institutionalized among parents.